Cerpen-cerpen Pujangga Baru - Mantik, Maria Josephine Kumaat (Wedatama Widya Sastra, 2006)
Revision of the author's thesis (Sarjana)–Universitas Indonesia, 1981
Includes bibliographical references (p. 52-53)
Keywords: 653; s; Indonesian short stories; history and criticism